2022
DOI: 10.3390/molecules27217389
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pineapple Waste as Fuel in Microbial Fuel Cell for the Generation of Bioelectricity

Abstract: The excessive use of fossil sources for the generation of electrical energy and the increase in different organic wastes have caused great damage to the environment; these problems have promoted new ways of generating electricity in an eco-friendly manner using organic waste. In this sense, this research uses single-chamber microbial fuel cells with zinc and copper as electrodes and pineapple waste as fuel (substrate). Current and voltage peaks of 4.95667 ± 0.54775 mA and 0.99 ± 0.03 V were generated on days 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The optimal operating valu of each MFC vary, and different types of substrates used with different pH have be found in the literature; one of the main reasons for this phenomenon is that the microo ganisms are different and each one grows at specific pH conditions, affecting the syste performance [41,42] To calculate the internal resistance of the MFC-SC, Ohm's Law (V = IR) was used, where the voltage values were placed on the "y" axis and those of the electric current on the "x" axis, which when performing a linear adjustment, the slope of the line is the internal resistance of the system, see Figure 4a. Based on the work carried out by Christwardana et al (2020), this method represents an effective tool for the in-depth study of MFCs [16,44], as unlike the electrochemical impedance method (EIS) used in other investigations, internal resistance is obtained more directly. The IES method allows us to find the different components of the internal resistance, such as the resistance of charge transfer, diffusion, and resistance of the substrate, which is obtained with the intersection of the Nyquist curve with the "x" axis measured from the origin.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal operating valu of each MFC vary, and different types of substrates used with different pH have be found in the literature; one of the main reasons for this phenomenon is that the microo ganisms are different and each one grows at specific pH conditions, affecting the syste performance [41,42] To calculate the internal resistance of the MFC-SC, Ohm's Law (V = IR) was used, where the voltage values were placed on the "y" axis and those of the electric current on the "x" axis, which when performing a linear adjustment, the slope of the line is the internal resistance of the system, see Figure 4a. Based on the work carried out by Christwardana et al (2020), this method represents an effective tool for the in-depth study of MFCs [16,44], as unlike the electrochemical impedance method (EIS) used in other investigations, internal resistance is obtained more directly. The IES method allows us to find the different components of the internal resistance, such as the resistance of charge transfer, diffusion, and resistance of the substrate, which is obtained with the intersection of the Nyquist curve with the "x" axis measured from the origin.…”
Section: Results and Analysismentioning
confidence: 99%
“…One of the highest values found in the literature was the one reported by Simeon et al (2020), where they were able to generate 725 mV peaks using urine treatment waste as a substrate in their MFC-SC with carbon electrodes, showing an initial and final internal resistance of 269.94 and 1627.89 Ω (by polarization method), respectively, resistance values increase from your control sample to the highest concentration of substrate (368.56 to 676.43 Ω) [43]. Figure 4b shows the power density (PD) values as a function of current density (CD), achieving a maximum power density of 264.72 ± 3.54 mW/cm 2 at a current density of 4.388 A/cm 2 with a peak voltage of 879.56 ± 0.184 V. The high values shown are due to the high inherent conductivity of the electrodes used, since being metallic in nature they facilitate the passage of electrons within the electrical circuit [44]. Other researchers have managed to generate higher values, but with the help of catalysts or biocatalysts, for example, Yaqoob et al ( 2022) managed to generate a maximum power density of 41.58 mW/m 2 with an internal resistance of 813.73 Ω using food waste (rice mixed with curry, vegetables, fish, cabbage, bones, and sweet cake pieces) as a substrate in MFC with graphite rod electrodes, compared to his control sample of 14.1 mW/m 2 , the increase was notorious [45].…”
Section: Results and Analysismentioning
confidence: 99%
“…Likewise, Figure 3b shows the values of electrical conductivity, where the values increase from the first day (70.46 ± 1.73 mS/cm) to day 18 (140.07 ± 3.51 mS/cm) and then decrease slowly until the last day (45.98 ± 4.51 mS/cm). The increase in electrical conductivity values is due to the low electrical resistance of the substrate used, while these values begin to decline due to the sedimentation of organic compounds present in the waste used [42,43]. Substrate masses have also been reported to have a dependence on electrical conductivity According to Kalagbor et al (2020), this relationship is directly proportional because in their research, the masses increased from 1 to 12 Kg and their electrical conductivity values increased from 787.6 ± 475.89 to 1282.9 ± 492.94 mS/cm.…”
Section: Results and Analysismentioning
confidence: 99%
“…It has been reported that in 100 g of this fruit, there is water (87 g), protein (1.1 g), fat (0.4 g), fiber (3 g), carbohydrates (11 g), iron (1.9 mg), vitamin B1 (0.04 mg), vitamin B2 (0.05 mg), vitamin B3 (0.16 mg), vitamin C (20.5 mg), calcium (8.5 mg), and phosphorus (22.5 mg), which have appropriate properties for medical and diuretic uses for the benefit of people [21,22]. The increase in the consumption of this fruit has generated an increase in waste products, creating a great problem for farmers and companies dedicated to the export and import of the fruit [23,24]. The use of organic waste, mainly fruit and vegetable waste, as fuel creates a great opportunity for governments and companies to reuse their own waste, even more so if this technology can be scaled for large quantities.…”
Section: Introductionmentioning
confidence: 99%